The Meaningful-Rhizomatic Paradigm of Alternative Education in the Tanoker Ledokombo Community - Moh Irsyad Fahmi MR; Saliman; Sudrajat; Satriyo Wibowo; Danang Ade Agustinova (Universitas Negeri Yogyakarta, 2025)
This study examines alternative education practice at the Tanoker Community in Ledokombo, Jember, East Java, through the lens of a meaningful-rhizomatic paradigm that integrates Ausubel's meaningful learning with the rhizomatic learning developed by Deleuze and Guattari and extended by Cormier. Using a qualitative grounded theory design, data were collected over seven months through participatory observation, in-depth interviews with 24 purposively and theoretically sampled informants, four focus group discussions, and documentation study, then analyzed through open, axial, and selective coding. Findings show that learning at Tanoker embodies five interrelated elements: egrang (traditional stilt-walking) as a cultural tool integrating cognitive, affective, and psychomotor dimensions; a non-hierarchical learning structure with multiple entry points; learning as a socio-communal process in which knowledge is collectively constructed; learning tightly connected to local reality and context; and collaborative parenting (pengasuhan gotong royong) as a supporting ecosystem. Rhizomatic characteristics manifest through multidirectional connectivity, heterogeneity of actors and methods, multiplicity of learning pathways, and adaptive resilience (asignifying rupture). Meaningfulness was experienced across cognitive, affective, social, and cultural dimensions by children, parents, facilitators, and the wider community. The study contributes a six-component operational model — core learning, child organization, parent empowerment, formal-informal integration, cultural celebration, and community-based tourism — offering a theoretically grounded, fifteen-year-tested reference for developing community-based alternative education in other contexts.